Population status and breeding ecology of Black Kite Milvus migrans (Boddaert, 1783) in Pokhara Valley, Nepal - Khand, Namuna; Adhikaree, Shaligram; Kharel, Milan; Gautam, Ramji (Our Nature, 2021)
The present study attempted to provide basic knowledge on population status, breeding success and general behaviours of Black kites in the Pokhara Valley of Nepal. Nesting and roosting sites were directly observed to count the bird in the fields during the study period from December 2019 to May 2020. A total of 308 individuals of Black kites were recorded. The highest and least number was recorded in February (n=67) and May (n=31) respectively. The breeding success was found to be 47.22%. The average height, girth and canopy cover of the nesting tree were found at 16.59m, 2.23m and 63.30% respectively. About 67% of nests observed were found active during the breeding season. The Spearman rank correlation coefficient showed a perfect positive relationship between the number of chicks and the number of the nest (r = 1). Bombax ceiba and Dalbergia sissoo were the trees on which the maximum number of nests were observed.